2019
DOI: 10.3311/ppch.13767
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Modeling Study of CO-Selective Catalytic Reduction of NO Over Perovskite-Type Nanocatalysts

Abstract: In this work LaFeO3, LaFe0.7Mn0.3O3 and LaMn0.7Fe0.3O3 nanocatalysts with perovskite structures have been synthesized by sol-gel method. The selective catalytic reduction of NO with CO (CO-SCR) using synthesized nanocatalysts was investigated in a plug flow reactor. The kinetics of CO-SCR process was studied and three kinetic models were used to describe the behavior of the system, including power low model (PLM), kinetic model 1 (KM1) and kinetic model 2 (KM2). The KM1 was the best model with correlation coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…When the molar ratio of cobalt ions to nickel ions is 1:1, the purification efficiency of La 2 NiCoO 6 on PM can reach 98.2%. Shiva Abedi et al [9] synthesized LaFeO 3 , LaFe 0.7 Mn 0.3 O 3 , and LaMn 0.7 Fe 0.3 O 3 nano-scale perovskite-type catalysts with different doping amount by sol-gel method, the CO was used as a reducing agent to selectively reduce NO through simulation experiments, in addition to studying the function of synthesized catalysts and finding the optimal catalyst in the CO-SCR process by XRD, SEM characterization methods, and chemical reaction kinetic model. The results showed that the conversion efficiency of CO and NO increased with the synergistic effect of manganese ions and iron ions.…”
Section: Introductionmentioning
confidence: 99%
“…When the molar ratio of cobalt ions to nickel ions is 1:1, the purification efficiency of La 2 NiCoO 6 on PM can reach 98.2%. Shiva Abedi et al [9] synthesized LaFeO 3 , LaFe 0.7 Mn 0.3 O 3 , and LaMn 0.7 Fe 0.3 O 3 nano-scale perovskite-type catalysts with different doping amount by sol-gel method, the CO was used as a reducing agent to selectively reduce NO through simulation experiments, in addition to studying the function of synthesized catalysts and finding the optimal catalyst in the CO-SCR process by XRD, SEM characterization methods, and chemical reaction kinetic model. The results showed that the conversion efficiency of CO and NO increased with the synergistic effect of manganese ions and iron ions.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many nanosized CO-SCR denitrification catalysts have been prepared using traditional synthesis methods, such as precipitation, , hydrothermal, , impregnation, , and sol–gel , methods. For instance, Ni­(Pt)/Al 2 O 3 catalysts were prepared by the sol–gel method, among which NiPt/Al 2 O 3 and Pt/Al 2 O 3 catalysts showed an excellent denitrification performance due to the interaction and synergy between Pt or Ni nanoparticles and the Al 2 O 3 carrier .…”
Section: Introductionmentioning
confidence: 99%